Gender, feminism, and the British left, 1944-1991. - Communist Party of Great Britain; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
This collection contains records compiled by the Communist Party of Great Britain's (CPGB) Women's Department during the period 1944-1991. These records include minutes, agendas, and promotional materials from various women's campaigns, events, and conferences. They also include copies of Link, the party's women's magazine, and Red Rag, a controversial journal published by the party's more militant feminist members.
Date range: 1944-1991.
Keywords: Women and communism; Communism -- Great Britain -- History -- Sources